Diversification and Earnings Management at U.S. Bank Holding Companies - Teclezion, Mussie (Journal of Accounting and Finance, 2023)
This study looks at the effects of diversification on bank earnings management practices using a sample of banking holding companies (BHCs) reporting in the U.S. over the 2001 to 2020 period. Loan diversification and noninterest income diversification are associated with a substantial reduction in earnings management at banking firms. Earnings management drops by an average of 1.86 % at banking firms pursuing the two diversification measures, peaks during recessionary periods and recedes in expansionary times. Our empirical evidence implies that these diversification measures are associated with lower corporate opacity in diversified BHCs. Thus, we infer that broadly diversified banking firms are likely to have stable earnings through offsetting losses and gains. Results have important implications for enhancing governance policies at banking firms.